Poverty in Latin America Sources of Welfare Disparities in Ecuador - Lopez-Acevedo, Gladys (The World Bank, 2009)
This paper contributes to the analysis of spatial poverty in Ecuador by deepening the understanding of the constraints faced by the poor in the country through an investigation of the role of portable characteristics (human capital) and geography in explaining welfare. At the national level, the results indicate that these characteristics explain 72 percent of the differences in welfare level between urban and rural areas, while returns to these characteristics account for 28 percent of the difference. Comparing a leading and a lagging region, such as the coast versus the Amazon, the characteristics explain about 90 percent of the welfare differential in urban areas, while the returns explain about 30 percent of the welfare differential in rural areas. Among the characteristics analyzed, education is the most important variable for explaining differences in living conditions between urban and rural areas in Ecuador